IMPACT OF BENZYL BUTYL PHTHALATE ON HAEMATOLOGY AND METABOLIC ENZYMES OF Clarias gariepinus - IDOWU, A. A.; OLUJIMI, O. O.; EDUNJOBI, G. O.; TOWOLAWI, A. T; AKINDE, A. O.; EZERI, G. N. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2021)
Benzyl butyl phthalate (BBP) is used in plastic industry and leaches into the environment through effluent and indiscriminate dumping of plastic wastes with possible deleterious effects on fish and other aquatic animals. Standard solution of 100 mg/ L was prepared from 10 mg of BBP stock solutions dissolved in acetone as carrier agent, and the used treatments were determined after conducting range finding test. Toxicity of various treatments: 0.1, 0.2, 0.8 and 1.6 µg/ L and control were investigated using haematology and metabolic enzymes as indicators in 150 juveniles of Clarias gariepinus. Each treatment was arranged in triplicates containing 10 fish samples each. Data obtained were subjected to descriptive and inferential statistics and tested at 0.05 significant level. Results showed that the dissolved oxygen in the fish tanks reduced gradually over the 4 days (96 h) of the experiment. There were increases in the levels of red blood cell (2.32-3.57 x1012/ L) and lymphocytes (58.1-63 %) but decrease in eosinophils (3.00-2.00 %). Levels of all the four metabolic enzymes gradually reduced (AST: 1001-890, ALT: 45.2-18.5, ALP: 62.60-17.15, and LDH: 925-906 U/ L) as the BBP treatment levels increased when compared to the control. Such observations might result from the efforts of the experimental fishes to subdue the toxicological effects of the BBP treatments. Usage of BBP in plastic manufacturing industries because of its cost-effectiveness should be replaced with environment-friendly alternatives such as thermoplastic elastomers.